Inflation persistence and price-setting behaviour in the euro area: a summary of the Inflation Persistence Network evidence - Filippo Altissimo; Michael Ehrmann; Frank Smets (National Bank of Belgium, 2006)
This paper provides a summary of current knowledge on inflation persistence and price stickiness in the euro area, based on research findings that have been produced in the context of the Inflation Persistence Network. The main findings are: i) Under the current monetary policy regime, the estimated degree of inflation persistence in the euro area is moderate; ii) Retail prices in the euro area are more sticky than in the US; iii) There is significant sectoral heterogeneity in the degree of price stickiness; iv) Price decreases are not uncommon. The paper also investigates some of the policy implications of these findings
Keywords: E31; E42; E52; 330; price-setting; inflation persistence; monetary policy; EMU; Inflation; Inflationskonvergenz; Inflationsbekämpfung; Preisrigidität; Preismanagement; Eurozone; Geldpolitik; EU-Staaten